2011
DOI: 10.1021/jp112236n
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Carbon-Based Fuel Cell Catalyst Support Structures via Nitrogen Functionalization. II. Investigation of Durability of Pt–Ru Nanoparticles Supported on Highly Oriented Pyrolytic Graphite Model Catalyst Supports As a Function of Nitrogen Implantation Dose

Abstract: Nitrogen functionalization of carbon-based support materials for lowtemperature fuel cell catalysts has been shown to improve catalystÀsupport interactions and therefore enhance both the performance and durability of the supported electrocatalyst. While previous work has focused on pure Pt electrocatalysts, this work focuses on understanding the role of nitrogen functionalization on the durability of PtÀRu alloy nanoparticle catalysts. A well-defined model catalyst system approach is used by employing highly o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 38 publications
1
55
0
Order By: Relevance
“…It was suggested that that these defects limit nanoparticle agglomeration, likely serving as trapping sites. 16,28 There is some debate as to the actual functional groups present in these types of systems and some recent studies have suggested these nitrogen clusters may be the start of a structures observed in carbon nitride films. 25 TEM images acquired from the post-modified catalyst sample are shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…It was suggested that that these defects limit nanoparticle agglomeration, likely serving as trapping sites. 16,28 There is some debate as to the actual functional groups present in these types of systems and some recent studies have suggested these nitrogen clusters may be the start of a structures observed in carbon nitride films. 25 TEM images acquired from the post-modified catalyst sample are shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that the main difference between the two catalysts is metal surface area, a conclusion that is substantiated by the TEM comparison of the two samples (Figure 2). In addition, XPS19 also indicates a change in the surface content. The total amount of Pt and Ru determined from XPS of the N‐doped PtRu/C is 8.2 vs. 7.2 at % for the undoped PtRu/C.…”
Section: Comparison Of Our Admfc Performance With Some Literature Datamentioning
confidence: 99%
“…have exhibited improved electrochemical ability ,. Heteroatom doped the carbon support matrix always led to the enhanced charge density and catalytic activity .Meanwhile, the altered electronic properties also facilitate the interaction between metal atom (such as Pt) and carbon support matrix which acts as a “cross‐linking agent” to prevent Pt nanoparticles agglomeration by the formation covalent bond ,. Recently, Sahu et al have prepared the nitrogen and fluorine co‐doped graphite nanofibers (NF‐GNFs) and applied as a highly corrosion resistant support matrix to disperse Pt nanoparticles .…”
Section: Introductionmentioning
confidence: 99%